2016
DOI: 10.3390/beverages2030017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steep Time on Polyphenol Content and Antioxidant Capacity of Black, Green, Rooibos, and Herbal Teas

Abstract: Potential health benefits of tea consumption are often attributed to the antioxidant activity of polyphenols. Whether steep time, often variable in a real-life situation, makes a biological difference in terms of polyphenol content and antioxidant activity is uncertain. The study objective was to characterize eight popular and commercially available teas for total polyphenol content (TPC) and antioxidant capacity in relation to steep time. Dragonwell (DW), Sencha (S), English Breakfast (EB), Golden Monkey (GM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 46 publications
(45 reference statements)
8
46
1
Order By: Relevance
“…Steep time was studied from 1 to 10 min at 1-min intervals, thus mimicking steep times often used by consumers. This study showed that over 50% of polyphenols were released in the initial 5 min of steep time and that TPC increased in a nonlinear relationship for all tea types tested [13]. Interestingly, longer steep time was not associated with greater antioxidant capacity (measured as the percent inhibition of the free radical DPPH) when the polyphenol content was standardized, but tea types did differ in their antioxidant capacity.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Steep time was studied from 1 to 10 min at 1-min intervals, thus mimicking steep times often used by consumers. This study showed that over 50% of polyphenols were released in the initial 5 min of steep time and that TPC increased in a nonlinear relationship for all tea types tested [13]. Interestingly, longer steep time was not associated with greater antioxidant capacity (measured as the percent inhibition of the free radical DPPH) when the polyphenol content was standardized, but tea types did differ in their antioxidant capacity.…”
Section: Introductionmentioning
confidence: 70%
“…The methods used in the current experiments have been described in detail previously [13], and only minor changes have been made to the apparatus to allow the steeping of tea prepared from tea bags, which requires a larger vessel than that required for loose-leaf products. Tea samples consisted of Orange Pekoe (OP) or Green (G) teas, or Red Rooibos (RR), Peppermint (P), or Chamomile (C): all products were purchased from a local supplier and prepared according to the manufacturers recommendations (see Tables 1 and A3 for tea product details).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations